Identification of first order plus dead time for a pH neutralization process using open loop test - Zainal, Azavitra; Wahab, Norhaliza Abdul; Yusof, Mohd Ismail; Razali, Mashitah Che (2024)
In this paper, a systematic method for determining the mathematical model for the pH neutralization process is proposed by applying system iden- tiﬁcation techniques to the controller design requirements. The identiﬁcation is conducted experimentally using an actual pilot plant and analysis is performed using MATLAB toolbox for system identiﬁcation. The identiﬁcation is based on the ﬁrst order plus dead time (FOPDT) method and subsequent application of model estimation and validation tests. In this study, pH is a controlled variable and alkali dosing pump stroke rate is a manipulated variable. The acid dosing pump stroke rate is ﬁxed at 10%. Four open-loop step response experiments were conducted in which the alkali dosing pump stroke rate was set at 30% (Set A), 40% (Set B), 50% (Set C), and 60% (Set D). Based on the best ﬁt performance criteria, Set B, Set C and Set D show approximately the same results. Frequency response analysis was performed using Bode plot and Nyquist diagram to deter- mine the stability. The results show that Set B is more stable than Set C and Set D. The stability criterion is important because the obtained FOPDT model is used for controller design.